2017
DOI: 10.3390/s17040746
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Lycopene, β-Carotene, and Total Soluble Solids in Intact Red-Flesh Watermelon (Citrullus lanatus) Using On-Line Near-Infrared Spectroscopy

Abstract: A great interest has recently been focused on lycopene and β-carotene, because of their antioxidant action in the organism. Red-flesh watermelon is one of the main sources of lycopene as the most abundant carotenoid. The use of near-infrared spectroscopy (NIRS) in post-harvesting has permitted us to rapidly quantify lycopene, β-carotene, and total soluble solids (TSS) on single intact fruits. Watermelons, harvested in 2013–2015, were submitted to near-infrared (NIR) radiation while being transported along a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 54 publications
0
21
0
2
Order By: Relevance
“…In the case of in-line applications the situation is similar: the predominant acquisition modes are reflectance, used in all in-line applications with olives (Salguero-Chaparro et al, 2012, and the transmittance mode in the case of pears (Xu et al, 2012;Sun et al, 2016). Examples of both acquisition modes were found in in-line applications with watermelon (Jie et al, 2014;Tamburini et al, 2017) and apple (McGlone et al, 2005;Shenderey et al, 2010;Ignat et al, 2014), but nectarines were the only example found that employed the interactance mode (Golic & Walsh, 2006).…”
Section: Comparison Between Off-line and In-line Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of in-line applications the situation is similar: the predominant acquisition modes are reflectance, used in all in-line applications with olives (Salguero-Chaparro et al, 2012, and the transmittance mode in the case of pears (Xu et al, 2012;Sun et al, 2016). Examples of both acquisition modes were found in in-line applications with watermelon (Jie et al, 2014;Tamburini et al, 2017) and apple (McGlone et al, 2005;Shenderey et al, 2010;Ignat et al, 2014), but nectarines were the only example found that employed the interactance mode (Golic & Walsh, 2006).…”
Section: Comparison Between Off-line and In-line Applicationsmentioning
confidence: 96%
“…The spectra were pre-treated using baseline offset correction (BOC). Recently, Tamburini et al (2017) developed an NIR in-line system to determine lycopene, β-carotene, and total soluble solids content in red-flesh watermelons in the selected wavelength range from to 1,700 nm in reflectance mode. Watermelons were transported along a conveyor belt system at different speeds (2,100, 2,400 and 2,700 rpm).…”
Section: Comparison Between Off-line and In-line Applicationsmentioning
confidence: 99%
“…Moreover, they preserve the sample fruit that would be wasted if destructive methods were used. In postharvest storage, visible and near-infrared spectroscopy (Vis-NIRS) can be applied in various forms where fruit would be passed under a radiation chamber and be analysed for physical, chemical and organoleptic properties whilst rolling on sorting belts [8]. The Vis-NIRS holds many advantages over destructive or contact techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining components is a rich source of bioavailable compounds, including lycopene, vitamins A and C, and the amino acid L-citrulline. Lycopene has been shown to exhibit anti-tumor, anti-inflammatory and anti-obesity effects and L-citrulline is known to have diuretic effects [7,8].…”
Section: Introductionmentioning
confidence: 99%